Opening Europe's telephone business to competition. - Tandon, V.
On January 1st 1998, by decision of the European Union's 15 member states, all of their telecommunications markets were to have been opened to full competition. In practice, it will take longer in many of the countries, sometimes quite a bit longer. The objective was to create a deregulated and harmonized single market in telecommunications. The former phone monopolies lost most of their exclusive rights and new operators were given the right to compete within a pro-competitive framework. In time, the 15 countries in the European Union (EU) will become a single, unified telecommunications market. By year-end, 13 will be open to competition (Portugal and Greece have received extensions to 1 January 2000 and 1 January 2001, respectively). The new regime will pit existing telecommunications players (such as the former telephone monopolies, cable TV operators, managed network service providers, foreign telecom operators, and major Internet service providers) against new players, including rail and power companies and entrants backed by industrial interests. All are fighting for a share of a European telecommunications market estimated at US 105-110 billion dollars.
Keywords: European Union; Internet service providers; Cable TV operators; Competition; Deregulated single telecommunications market; Foreign telecom operators; Former telephone monopolies; Harmonized single telecommunications market; Managed network service providers; Power companies; Rail companies; Telecommunications markets; Telephone business; Unified telecommunications market